Eating skills in children with autism via video modeling: an evaluation of face and content validation - Hasrul bin Hosshan, Nurbieta binti Abd Aziz, Abdul Halim Masnan, Norsayyidatina binti Che Rozubi, Mohd Muslim bin Md Zalli (Tanjung Malim, 2024)
Eating skills in children with autism via video modeling: an evaluation of face and content validation by Hasrul bin Hosshan, Nurbieta binti Abd Aziz, Abdul Halim Masnan, Norsayyidatina binti Che Rozubi, Mohd Muslim bin Md Zalli